Discovery of high-performance thermoelectric copper chalcogenide using modified diffusion-couple high-throughput synthesis and automated histogram analysis technique. Issue 9 (6th August 2020) - Deng, Tingting; Xing, Tong; Brod, Madison K.; Sheng, Ye; Qiu, Pengfei; Veremchuk, Igor; Song, Qingfeng; Wei, Tian-Ran; Yang, Jiong; Snyder, G. Jeffrey; Grin, Yuri; Chen, Lidong; et al.
Abstract : A modified HTP synthesis method and an automated histogram analysis technique are developed to screen the new stable ternary CTS compound Cu7 Sn3 S10 . Abstract : Discovery of novel high-performance materials with earth-abundant and environmentally friendly elements is a key task for civil applications based on advanced thermoelectric technology. Advancements in this area are greatly limited by the traditional trial-and-error method, which is both time-consuming and expensive. The materials genome initiative can provide a powerful strategy to screen for potential novel materials using high-throughput calculations, materials characterization, and synthesis. In this study, we developed a modified diffusion-couple high-throughput synthesis method and an automated histogram analysis technique to quickly screen high-performance copper chalcogenide thermoelectric materials, which has been well demonstrated in the ternary Cu–Sn–S compounds. A new copper chalcogenide with the composition of Cu7 Sn3 S10 was discovered. Studies on crystal structure, band gap, and electrical and thermal transport properties were performed to show that it is a promising thermoelectric material with ultralow lattice thermal conductivity, moderate band gap, and decent electrical conductivity. Via Cl doping, the thermoelectric dimensionless figure of merit zT reaches 0.8 at 750 K, being among the highest values reported in Cu–Sn–S ternary materials. The modified diffusion-couple high-throughput synthesis method and automated histogram analysis technique developed in this study also shed light on the development of other advanced thermoelectric and functional materials.